Relationships among Shopping Quality and Corporate Social Responsibility of Shopping Centers and Consumer Satisfaction: Case from Novi Sad (Serbia) - Ivana Blešic; Aleksandra Dragin; Jelica Markovic; Slobodan Cerovic; Lukrecija Deri (Amfiteatru Economic Journal, 2014)
Taking into consideration satisfied customer as necessary for business maintenance, companies are trying to discover determinants which have the biggest influence on their consumer satisfaction. Here are presented two factors that have influence on consumer satisfaction in shopping centers: quality of shopping and corporate social responsibility. In this research, each of these factors had six elements. The results of the regression analysis are that “Value for money in stores” (beta=0.387, p=0.000) has the greatest impact on satisfaction when shopping quality performance is concerned, and that “Retailer support for (national/local) cultural and sport events“ (beta=0.333, p<0.001) has the greatest impact on satisfaction in the case of CSR performance. Further analysis showed the difference in consumer perception of corporate social responsibility, depending on their occupation and level of education. It is also important to mention that consumers with environment and empathic concern have higher scores perception of CSR. However, there is not statistically important difference in consumer perception of shopping quality in shopping centers
Keywords: M14; 330; Corporate social responsibility; Shopping centers; Shopping quality; Consumer satisfaction